1990
DOI: 10.1080/00986449008940553
|View full text |Cite
|
Sign up to set email alerts
|

Solids Circulation in Spouted and Spout-Fluid Beds With Draft-Tubes

Abstract: Muir, J. R. (1988). Solids circulation in spouted and spout-fluid beds with draft-tubes (Unpublished master's thesis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 14 publications
(11 reference statements)
8
56
0
Order By: Relevance
“…One observes periodic pulsations of bed-flow at frequencies ranging from 4 to 12 Hz. This phenomenon was observed by Muir et al (1990), who found that for their apparatus configuration the flow of particles occurred at frequencies ranging from 8 to 12 Hz (increasing with increasing gas flow) over the range of flows studied. Moreover, they observed that the solids crossed into the jet and covered the inlet.…”
supporting
confidence: 53%
“…One observes periodic pulsations of bed-flow at frequencies ranging from 4 to 12 Hz. This phenomenon was observed by Muir et al (1990), who found that for their apparatus configuration the flow of particles occurred at frequencies ranging from 8 to 12 Hz (increasing with increasing gas flow) over the range of flows studied. Moreover, they observed that the solids crossed into the jet and covered the inlet.…”
supporting
confidence: 53%
“…At the same time, a continuous percolation of gas from the spout region to the annular region exists. If the operational bed height is larger than the maximum spoutable bed depth H m , the spout cannot support the bed, and a transition from spout to collapse occurs [2][3]. In addition, it is also reported that the elevated temperature causes a decrease in H m and the stable spout eventually disappears at temperatures above 420°C despite the changing operating variables [4].…”
Section: Introductionmentioning
confidence: 99%
“…Those existing studies mainly focused on the dependence of solid circulation rate on operating variables such as draft tube diameter, particle size, length of entrainment region, gas velocity, etc. [22][23][24][25][26][27]. It is also impossible to extend empirical correlations and theoretical analyses developed from the experiments of conventional systems to the applications of DTSBs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work (e.g. Muir et al, 1990) has shown that spouting can be enhanced by the insertion of an impermeable draft tube. Experiments were therefore carried out on dry spouting of the 6 mm polystyrene spheres using the draft tube set-up described above.…”
Section: Enhancement Measurementsmentioning
confidence: 99%